Physiological responses to full and segmented duet routines in elite artistic swimmers - Iglesias, X.; Rodríguez-Zamora, L.; Carrasco-Marginet, M.; Irurtia, A.; Rodríguez, F. A.; Fernández-Jarillo, I.; Chaverri, D. (PLOS ONE, 2025)
Artistic swimming combines prolonged breath-hold periods with high-intensity movements, resulting in unique physiological demands. Direct measurement of key variables such as oxygen uptake (VO2) during routines is limited by frequent immersion. However, VO2 monitoring is essential for understanding the balance between aerobic and anaerobic energy contributions, guiding training strategies and reducing injury risk. This study aimed to analyze the acute physiological responses, VO2, blood lactate concentration, and heart rate, during free duet routines in elite artistic swimmers, using a segmented protocol that emphasized the two longest apneas. Sixteen elite artistic swimmers performed both complete and segmented versions of the routine. VO2 was estimated using retro-extrapolation, while lactate was measured after each phase, and heart rate was continuously monitored. The protocol included six measurement points: pre-routine, pre- and post-apnea 1 and 2, and post-routine. VO2 increased rapidly, reaching nearly 90% of VO2 peak within 67 seconds (mean: 61.8 ± 15.1 mL/min/kg). Blood lactate concentration rose progressively, peaking at 5.93 ± 1.41 mmol/L. Heart rate exhibited large fluctuations, with a maximum of 203.8 ± 5.0 beats/min and a minimum of 71.9 ± 16.6 beats/min, reflecting a bradycardic response during apneas. No significant changes were observed in VO2 or lactate between pre- and post-apnea values, as measured around the two longest apneas within the routine. These findings suggest that, under the specific conditions of this study, short-duration apneas (< 20 s) may be insufficient on their own to elicit distinct physiological shifts. However, the progressive increases observed in blood lactate and heart rate throughout the full routine suggest that the overall physiological load may be influenced more by sustained exercise intensity and the cumulative effect of repeated apneas than by isolated breath-hold events.